Vaccination coverage with the immunogen Abdala in adults of a family doctor office - Alfredo Hernández Magdariaga; Naifi Hierrezuelo Rojas; Ulises Gómez Soler; Clarisa Torres Tejera; Deborah Enrique Perera (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: In Cuba our own vaccines are developed, although the country has a great economic crisis and the material resources are limited. Objective: To describe the vaccination anti-COVID-19 campaign with Abdala in an adult population. Methods: A descriptive serial cases study was carried out in 616 patients over 19 years corresponding to the Family Doctor Office No. 5 of Ramón López Peña Teaching Polyclinic in Santiago de Cuba, who received the immunogen Abdala from June to August, 2021. Results: In the 616 adults that were immunized in the vaccine office of their family doctor office, there was a prevalence of the male sex (53.4 %), mainly 40 to 59 years (20.2 %). Among the most usual secondary effects we can mention pain in the place of the injection (23.1 %), followed by headache (12.2 %); nevertheless, all completed the vaccination scheme of 3 doses. In general, the 93.6 % of the adult population was vaccinated and 6.4 % didn't receive the immunization, mainly due to the history of infection by the SARS-CoV-2 (1.6 %), among other causes. Conclusions: The campaign was successful, because a high percentage of immunized people was reached, which is attributed to the active participation of the population and the health basic team.